NURSING STUDENT’S EXPERIENCE IN CARING CHILDREN WITH DISABILITY: A QUALITATIVE STUDY - Erawati, Erna; Keliat, Budi Anna (Sanata Dharma University Yogyakarta, 2018)
Caring children with intellectual disability remains a challenge for nursing students due to unprepared feeling and lack of experience. Therefore it is important for the nursing students to increase their self-awareness in caring children with intellectual disability through their clinical placement. The aims of this study are to explore the experience of the nursing students caring children with intellectual disability. A qualitative approach using a phenomenological was applied to explore the experience of the nursing students in caring children with intellectual disability. One time semi-structured interviewed were conducted. Data were collected through personal interviews about their experience and the transcripts of these interviews were subjected categorically. Data analysis identified the emerging themes as changing perception, communication challenges, and life value in caring children with intellectual disability. Findings suggest strategies to promote competencies of the nursing students in caring children with intellectual disability. DOI: https://doi.org/10.24071/ijiet.2018.020211